Human Resource Management to Improve the Quality of Education in Islamic Boarding School - Wafa Sopiulloh; Taufik Hidayat; Dewi Cahyani; Moh Ali (FKIP - Universitas Riau, 2026)
Human resource management (HRM) constitutes a strategic component in efforts to improve the quality of education, including within pesantren institutions characterized by their religious foundations and distinctive cultural traditions. This study aims to examine relevant and effective HRM practices that support the enhancement of educational quality in pesantren. Employing a qualitative approach through a literature-based study, this research reviews various scholarly works, previous empirical findings, and academic documents focusing on HRM within pesantren-based educational institutions. The analysis indicates that improving educational quality can be achieved through well-directed planning of educator needs, recruitment processes that emphasize competence and integrity, the implementation of continuous training and development programs, and systematic performance evaluations. Additionally, the leadership of the kiai plays a pivotal role in establishing strategic policies and fostering an organizational climate conducive to optimizing HRM performance. These findings underscore that systematic and contextually appropriate HRM constitutes a critical element in enhancing instructional effectiveness and institutional management within pesantren.